Emergent Disabilities and Centers for Independent Living: The Case of Chronic Fatigue Syndrome - Taylor, Renee; Eisele, Heather (Disability Studies Quarterly, 2003)
Over 500 Centers for Independent Living exist internationally. Centers for Independent Living are community-based, empowerment-oriented organizations that provide advocacy and linkage to resources for individuals with a wide range of disabilities. Historically, people with invisible disabilities such as chronic fatigue syndrome (CFS) have not made extensive use of Centers for Independent Living, and have not been formally introduced to the independent living philosophy. Conversely, Centers for Independent Living have encountered difficulty outreaching to and serving individuals with CFS, and have not been adequately informed about their resource needs and entitlements. The purpose of this study was to assess attitudes and knowledge about chronic fatigue syndrome among staff members of a Center for Independent Living before and after an educational intervention designed to raise awareness about CFS and provide guidance about the resource needs and entitlements of the CFS population. Before the intervention, over half (62%) of the staff members regarded CFS as having a biological cause, most considered CFS as a severe or very severe condition (76%), and most (74%) were of the opinion that an empowerment-oriented, independent living philosophy would benefit individuals with CFS. As a result of the intervention, all (100%) respondents either gained increased factual information about CFS, increased empathy toward individuals with CFS, or increased general awareness of CFS. Most (67%) respondents reported that the intervention changed their prior level of awareness of CFS, empathy toward those with CFS, or awareness of the medical legitimacy of CFS. The implications of these findings are discussed in terms of their relevance for community-based alternatives to health care for individuals with emergent disabilities in the 21st century.